PENGARUH BURN OUT DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI PT. KERETA API INDONESIA (PERSERO) BAGIAN OPERASIONAL CABANG STASIUN TIGA GAJAH - Rosmala Dewi; Andri Oganda; Rr. Dimas Veronica Priharti; Rani Anwar (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2022)
The analytical tool used in this study is multiple linear regression. The purpose of this study was to determine the Influence of Burn Out and Workload on the Performance of Operational Personnel at PT. Kereta Api Indonesia (Persero) Tiga Gajah Station Branch. The t-value of the burn out variable is -1.233> -2.05183, then Ho is accepted and Ha is rejected, meaning that partially there is no significant influence of burn out (X1) on performance (Y). The t-value of the workload variable is 3,622> 2.05183. Then Ho is rejected and Ha is accepted, meaning that there is a significant influence of workload (X2) on employees’ performance (Y). The results of the F test analysis show that burn out and workloads simultaneously have a significant influence on performance, where the F count of (17,613) is greater than the F table (3.35). The results of the coefficient of determination R Square of 0.674, meaning that the amount of contribution or the amount of influence of the independent variable that is burn out, workload, and the dependent variable is performance by 67.4% while the remaining 32.6% is determined by other variables not included in the research model this is like ability and expertise, knowledge, work design, personality, organizational culture, and job satisfaction (Kasmir, 2016: 189).